Detection and Management of Intraoperative Pneumothorax during Laparoscopic Cholecystectomy - Heyba, Mohammed (Case Rep Anesthesiol, 2020)
Intraoperative pneumothorax is a rare but potentially lethal complication during general anesthesia. History of lung disease, barotrauma, and laparoscopic surgery increase the risk of developing intraoperative pneumothorax. The diagnosis during surgery could be difficult because the signs are often nonspecific. We report a case of a middle-aged gentleman who developed right pneumothorax during an elective laparoscopic cholecystectomy. The patient had no risk factors for adverse events during the preoperative assessment (ASA1). The patient underwent general anesthesia and was put on mechanical ventilation. The first signs of abnormality immediately after surgical port insertion were tachycardia and low oxygen saturation in addition to sings of airway obstruction. The diagnosis of pneumothorax was made clinically by chest auscultation and later confirmed by intraoperative chest radiograph. Supportive treatment was started immediately through halting the surgery and manually ventilating the patient using 100% oxygen. Definitive treatment was then done by inserting an intercostal tube. After stabilizing the patient, the surgery was completed; then, the patient was extubated and shifted to the surgical ward. Postoperative computed tomography (CT) scan was done and showed only minimal liver laceration. The patient was discharged after removing the intercostal tube and was stable at the follow-up visit. Therefore, it is important to have a high index of suspicion to early detect and treat such complication. In addition, good communication with the surgeon and use of available diagnostic tools will aid in the proper management of such cases.